Institutional Integrity and Academic Issues in Public Universities in Southwest Nigeria - Olugbenga Ajadi; Chinedu I. Okeke (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The reason for Nigeria's graduate unemployment rate is because quality of education offered graduates in Nigerian universities is challengeable and insufficient to fulfill the expectations of contemporary employment. The study investigated the composite contribution of the four admission criteria, as well as relative contribution of catchment area, merit, quota, and educationally less developed state criteria to the quality of Nigerian graduates. The study adopted survey research approach with a population of all undergraduate across the public universities in Nigeria. Stratified, purposeful and simple random technique was used to select 800 participants each from 400 level at the Ahmadu Bello University, Zaria and Obafemi Awolowo University, Ile-Ife, Nigeria. The universities are among the first-generation universities located in northern and southern parts of the country. The study found a significant composite contribution of the four government admission criteria to graduate quality. In addition, merit, quota and, catchment criteria have relative significant contribution with merit having the biggest contribution whereas the lowest and least relative significant contribution was made by ELDS. The study excluded other public universities outside the first-generation ones as well as private universities within defined time frame and geographic context. Future research could incorporate empirical investigations on the variables of the study in universities outside the first-generation and private